2010
DOI: 10.1186/1471-2458-10-270
|View full text |Cite
|
Sign up to set email alerts
|

Estimated birth weight and adult cardiovascular risk factors in a developing southern Chinese population: a cross sectional study

Abstract: BackgroundBirth weight is negatively associated with cardiovascular diseases and diabetes, but the associations are less well-established in developing populations where birth weight is often unavailable. We studied the association of birth weight and cardiovascular risk, using birth rank as an instrumental variable, in Southern China.MethodsWe used published data on birth weight by birth rank from an appropriate population and baseline data from the Guangzhou Biobank Cohort Study phases 2 & 3 (2005-8) to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
2
12
0
1
Order By: Relevance
“…Diabetes is a strong predictor of CAD/MI, however it is becoming increasingly evident that factors do not always have the same effect on diabetes and CAD/MI, such as lipids or statins29. Our findings for lipids are fairly consistent with well-conducted observational studies30 and instrumental variable analysis using birth rank as an instrument for birth weight9, which found no association of birth weight with HDL and triglycerides. Our findings do not exclude the possibility of a small association of higher birth weight with lower HDL-cholesterol.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Diabetes is a strong predictor of CAD/MI, however it is becoming increasingly evident that factors do not always have the same effect on diabetes and CAD/MI, such as lipids or statins29. Our findings for lipids are fairly consistent with well-conducted observational studies30 and instrumental variable analysis using birth rank as an instrument for birth weight9, which found no association of birth weight with HDL and triglycerides. Our findings do not exclude the possibility of a small association of higher birth weight with lower HDL-cholesterol.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings do not exclude the possibility of a small association of higher birth weight with lower HDL-cholesterol. Such an association, if it exists, might have been obscured by negative confounding by socio-economic position in previous observational studies30 and by lack of power in studies using instrumental variable analysis9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we found a J‐shaped relationship between birth weight and BMI at baseline, when participants were aged 40–74 years. Our finding of the lower birth weight–lower BMI relationship is in agreement with most previous studies conducted in Western populations, but is not consistent with studies conducted in Chinese adults . Based on data from the 2002 Chinese Nutrition and Health Survey, Yang et al found that compared with women born in 1964, those born during the worst famine years (1959, 1960, and 1961) had higher BMI and a higher prevalence of overweightedness as adults.…”
Section: Discussionsupporting
confidence: 67%
“…It has been suggested that adverse exposures in early life can “program” short stature and a predisposition to abdominal adiposity, as well as an insulin resistance and other cardiometabolic risk factors in adult life . Low birth weight has been associated with a higher risk of central obesity, measured as WHR, after adjusting for adult BMI, although results are not consistent . Low birth weight was also linked to larger WC and WHtR in Asian populations.…”
Section: Discussionmentioning
confidence: 97%